A new algorithm for feature selection based on rough sets theory - Yailé Caballero; Delia Álvarez; Analay Baltá; Rafael Bello; María García (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
Rough Sets Theory has opened new trends for the development of data analysis techniques. In this theory, the notion of reduct is very significant, but obtaining a reduct in a decision system is an expensive computing process although very important in data analysis and new discoveries. Because of this, it has been necessary to develop different variants to calculate reducts. The present work looks into the utility that offers Rough Sets in feature selection and a new method is presented with the purpose of calculate a good reduct. This new method consists of a greedy algorithm that uses heuristics to work out a good reduct in acceptable times. Experimental results obtained by using different data sets are presented.